Fertilization and population density in coro inbreds in Northeastern México. - Morales, Juan Antonio (2016)
Three coro inbreds (Zea mays L.) with different levels of N, P and population density were studied. The design used consisted of plots divided into randomized blocks where inbreds made up the main plot. Combinations of N, P and population density made up the small plot (a three-factorial central composed design was used for in this plot). Results showed a significant difference between inbreds; there was no evidence of interaction between treatments and inbred combination. A subsequent analysis showed that the stationary point was a saddle point. Another analysis was carried out in order to determine this point, and it was found that the route to highest yields tended towards N=83, P=4l, and a population density of 74,752 plants per hectare (pph). This contradicts the recommendation made for commercial coro in this region, which is N=140, P=40, and a population density of 55,000 pph.